2013
DOI: 10.1111/vox.12102
|View full text |Cite
|
Sign up to set email alerts
|

First comparative evaluation of a new leukapheresis technology in non‐cytokine‐stimulated donors

Abstract: Leukaphereses with the three devices resulted in almost equal total MNC yields. MNC products of the Spectra Optia and the Amicus could be used in preference for the monocyte enrichment by the Elutra system and the leukapheresis procedures could be also favourably applied in patients with low platelet counts. The COM.TEC is more efficient in monocyte and T-cell collection with the disadvantage of high residual non-target cell content in the products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 26 publications
3
34
3
Order By: Relevance
“…Some authors could demonstrate that the CBC values performed just before starting leukocytapheresis of all cell populations correlated significantly with their corresponding cell yield in the product . However, other authors found strong, medium, and no correlation between the cell counts obtained with CBC before performing leukocytapheresis and the number of cells collected. Taken together all previous data, there seem to be further variables, which influence the correlation between pre‐apheresis values and the corresponding cell yield.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors could demonstrate that the CBC values performed just before starting leukocytapheresis of all cell populations correlated significantly with their corresponding cell yield in the product . However, other authors found strong, medium, and no correlation between the cell counts obtained with CBC before performing leukocytapheresis and the number of cells collected. Taken together all previous data, there seem to be further variables, which influence the correlation between pre‐apheresis values and the corresponding cell yield.…”
Section: Discussionmentioning
confidence: 99%
“…Both are based on Ficoll density centrifugation, and significant evidence of their suitability has been provided. The Spectra Optia BMP is a new application for the relatively recent Spectra Optia apheresis device that was previously introduced . The package consists of the standard Spectra Optia MNC filler, the standard Spectra Optia IDL tubing set, and a large BM bag for recirculating of the (increasingly MNC‐deplete) BM suspension, as well as a software that provides fully automatic, photo detector–guided apheresis of the BM, physically highly analogous to MNC apheresis in stem cell donors.…”
mentioning
confidence: 99%
“…In contrast, Punzel et al [10] detected only a weak correlation between the CD3+ pre-apheresis values and the CD3+ cell yield in the product. Steininger et al [11] could show a significant correlation between the pre-apheresis cell count and the correspondent product cell yield for CD14+ but not for CD3+ cells. Taken together, there seem to be further variables, which influence the correlation between pre-apheresis values and the corresponding cell yield.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding the above, the CMNC program remains easier to monitor and can be controlled more precisely than the MNC program. In addition, previous studies focused mainly on the differences in leukapheresis procedures and their performance [11,12]. Only a few publications included the short-term impact of the procedure on the donor [5,13].…”
Section: Introductionmentioning
confidence: 99%